(untitled) (International Seven Journal of Health Research, 2023)
Acute cholecystitis is an acute inflammatory disease of the gallbladder, commonly caused by lithiasis. It is more prevalent in females, and one of its risk factors is obesity. In the vast majority of cases, symptoms include intense pain in the right hypochondrium or epigastrium, which may radiate to the back, associated with nausea, vomiting, diarrhea, hyporexia, fever and jaundice. The diagnosis is made through images, such as abdominal ultrasonography, which is considered a very efficient method for these cases, or computed tomography of the abdomen and in some situations through endoscopic examination (colonoscopy). The treatment is surgical. The patient in the case report in question had a cholecystocolic fistula, which is a rare complication of biliary lithiasis, which has variable and nonspecific clinical manifestations, and its diagnosis is often made incidentally in the perioperative period of its underlying cause. The most indicated treatment is cholecystectomy with closure of the fistula by videolaparoscopy